IMPLEMENTASI METODE BIL QOLAM TERHADAP KEMAMPUAN MEMBACA AL QUR’AN DI SMAI AL-MA’ARIF SINGOSARI MALANG - Muhammad Syukron Ni’am; Abdul Jalil; Mutiara Sari Dewi (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
This research starts from the background of the implementation of the Bil Qolam method in improving the reading of the Qur'an at SMAI Al-Ma’arif Singosari Malang. The purpose of this study was to determine the implementation of the Bil Qolam method and the results of the implementation of the method. This study uses a qualitative method with a descriptive model. Based on the results of the study and the data obtained, it shows that there is an increase in the quality of reading the Qur'an by looking at the assessment which has 10 assessment indicators.